Pengaruh Rasio Keuangan Terhadap Return Saham Pada Perusahaan Real Estate And Property Yang Terdaftar Di Bursa Efek Indonesia Periode Tahun 2017-2021 - Steward Christopher; Mega Amelia Putri; Jessica Jessica; Arie Pratania Putri; Debbi Chyntia Ovami (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The research objective was to test and analyze Return On Assets (ROA), Earning Per Share (EPS), Debt to Equity Ratio (DER) and Price to Book Value (PBV) affecting Stock Returns. The research method uses quantitative. The population of this study were all Real Estate and Property companies listed on the Indonesia Stock Exchange during the 2017-2021 period, totaling 81 companies and 7 companies as samples and 35 observations, and sampling was determined by the purposive sampling method. Data analysis used multiple linear regression analysis. Partial test results obtained t count value obtained t count 2.255019) > t table (2.042) and a significant value obtained 0.0335 <0.05, so Return On Assets (ROA) has a positive and significant effect on stock returns. Value t count is obtained for t count (-1.675670) > t table (2.042) and a significant value is obtained for 0.1068 > 0.05 then Earning Per Share (EPS) has no effect on Stock Returns. The t count value is obtained for t count 0.822924) > t table (2.042 ) and a significant value is obtained for 0.4187 > 0.05, then the Debt to Equity Ratio (DER) has no effect on Stock Returns. The t count value is obtained for t count 0.014168) > t table (2.042) and a significant value is obtained 0.9888 > 0.05, then the Price to Book Value ( PBV) has no effect on stock returns. The calculated F value is obtained for F count (1.732305) < Ftable (2.5335) and a significant value is obtained 0.175771> 0.05 then Return On Assets (ROA), Earning Per Share (EPS), Debt to Equity Ratio ( DER) and Price to Book Value (PBV) have no effect on Stock Return. Keywords: Return On Assets (ROA), Earning Per Share (EPS), Debt to Equity Ratio (DER), Price to Book Value (PBV), Stock Return